Characterization and microsatellite analysis for genetic diversity and bottlenecks of Spiti donkey - BEHL, RAHUL; SADANA, D K; BEHL, JYOTSNA; BANERJEE, PRIYANKA; JOSHI, JYOTI; VIJH, R K; ATTRI, P N; NADDA, SANJEEV; JOSHI, B K (The Indian Journal of Animal Sciences, 2017)
The Spiti donkeys distributed in Spiti and Yangthang regions of Himachal Pradesh were characterized for morphometric characteristics, management practices and utility. They were also evaluated for genetic diversity and bottlenecks using microsatellite markers. Spiti donkeys remain comparatively smaller in size with compact bodies usually covered with a thick coat of long hairs. The height at withers of male and female Spiti donkeys was 88.59±3.27 and 88.65±3.30 cm, respectively. The genomic DNA isolated from the blood samples collected from the 46 animals of this breed was amplified by PCR and resolved for alleles on automated DNA sequencer. The observed number of alleles ranged from 4 (VHL20, HTG6) to 10 (HTG7), with a mean of 6.33±1.72 alleles per locus. The observed heterozygosity ranged from 0.48 (NVHEQ54) to 0.89 (HTG7), with a mean value of 0.72±0.13. The mean FIS was 0.048 indicating moderate level of inbreeding. The normal 'L' shaped distribution of allelic frequency indicated towards absence of any recent genetic bottlenecks in the Spiti donkeys.